Welfare and work performance of public workers at UNHEVAL, Huánuco, 2019 - Agui-Ortiz, Alejandrina K. (2020)
The objective of the present research was to analyze the relationship between labor welfare and on labor performance of public workers at the Universidad Nacional Hermilio Valdizán de Huánuco during 2019. This was a quantitative, non-experimental approach with a descriptive, correlational, cross-sectional and prospective design. The population was composed of 71 workers, of whom 60 subjects were selected by non-probabilistic sampling, according to the convenience of the researcher. For data collection, an interview guide of general characteristics and two questionnaires were used, one on labor welfare and the other on labor performance of public workers, previously validated and validated, which were applied according to the ethical considerations of the research. The results showed that 96.7% (58) had an average performance and 63.3% (38) a high level of labor welfare. There was a significant relationship between high labor welfare and labor performance in the dimensions: job knowledge, autonomy, information management, responsibility, customer service attitude and communication [X2 = 12,100a, X2 = 21,700a, X2 = 19,300, X2 = 34,300, X2 = 11,100 and X2 = 12,900; gl = 2 with p ≤ 0.05]. Labor welfare was found to be independent of labor performance with respect to the dimensions: reliability and innovation-creativity [X2 = 0.562 and 0.100; gl = 4 and 2 and p = 0.703 and 0.951]. It is concluded that there is a statistically significant relationship between the welfare and labor performance of public workers of the UNHEVAL in Huánuco, during 2019